YBhg. Tan Sri Dr. Bashir Ahmad Abdul Majid, Chairman of Mass Rapid Transit Corporation Sdn. Bhd. (MRT Corp), visits FBM - UiTM, Faculty of Business and Management (UiTM, 2023)
On December 1st, 2023, the Chairman of Mass Rapid Transit Corporation Sdn. Bhd. (MRT Corp), Tan Sri Dr. Bashir Ahmad Abdul Majid, paid a visit to the Faculty of Business Management (FBM) with the aim of exploring opportunities for deeper collaboration between the two organizations. This collaboration is intended to provide students with greater exposure to the real working environment and develop their business skills and experience. During the visit, discussions centered around the importance of academic roles in the corporate world, which involves different values and priorities. The collaboration between corporations and academic institutions focuses on the combined development and sharing of knowledge, technology, and expertise. To ensure that FBM's content, delivery, and learning methods are in line with industry needs, collaboration with corporations is crucial.